Social and Psychological Mobilizers of Attitude towards Activity Sports: A Multi-Theory Perspective - Yongsheng Wang, Zhiguo Zhang , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
An individual’s attitude towards sports is formulated and conditioned by a variety of factors. Previous studies have shown that the attitude towards sports activities is conditioned by the individual as well as the social and psychological factors affecting the formulation of this attitude. Therefore, the present study was constructed to evaluate the impact of the social and psychological mobilizer’s influence on the formulation of an individual’s attitude towards sports participation. An empirical model based on the theory of planned behavior has been proposed, considering the influence of family support, social influence, self-efficacy and self-regulation on the attitude towards sports and perceived enjoyment has been introduced as a mediator. A sample consisting of 356 Chinese individuals was collected online from educational institutes. The analysis of the data was performed using SEM. The proposed model demonstrates that social factors influence the development of attitude towards sports activities in individuals. Psychological factors also demonstrated a significant association with attitude towards sports. The mediation of perceived enjoyment also showcased significant effects. The study is novel from the standpoint as it evaluates both the psychological and social factors along with the introduction of perceived enjoyment in mediation and produces new findings. The study holds important implications from a policy-making and managerial standpoint as well.